Removal of caffeine from water by combining dielectric barrier discharge (DBD) plasma with goethite - Jian Wang; Yabing Sun; Hao Jiang; Jingwei Feng (Journal of Saudi Chemical Society, 2017)
In this research, dielectric barrier discharge plasma was developed to cooperate with goethite for removing caffeine in aqueous solution. Goethite was characterized by X-ray diffraction and scanning electron microscopy. The effects of input power, initial concentration and catalysts concentration on the removal efficiency of caffeine were evaluated. Furthermore, the degradation pathways of caffeine were also discussed preliminarily. In the case of caffeine concentration at 50 mg L−1, the degradation efficiency of caffeine was improved from 41% to 94% after 24 min on the conditions of input power of 75 W by combining goethite catalysts (2.5 g L−1), while the energy efficiency could be enhanced 1.6–2.3 times compared to the single DBD reactor. The reaction mechanism experiments demonstrated that attack by hydroxyl radical and ozone was the main degradation process of caffeine in aqueous solution. These studies also provided a theoretical and practical basis for the application of DBD-goethite in treatment of caffeine from water.